Improving Problem-Solving Ability and Character in Subject-Specific Pedagogic with Heuristic Strategy - Yudi Darma; Dede Suratman; Ahmad Yani T.; Utin Desy Susiaty (JETL (Journal of Education, Teaching and Learning), 2019)
This study aimed mainly at producing Subject Specific Pedagogic (SSP) Statistics based on Character-filled Heuristic Strategies to Improve Students' Qualified Problem-Solving Ability built on the level of validity, practicality, and effectiveness. The study at this time was in synergy with the previous research as a new frame of mind that became the concept of development in achieving the main objectives. The present study employed a quantitative descriptive method with logical, analytical, and descriptive reasonings supported with relevant literature data. The instruments used were a test of problem-solving abilities and a questionnaire that was then analyzed descriptively and inferentially with two-way ANOVA formula. The study concluded that the heuristic strategy through the stages of identification, plan, do and check is an alternative solution to learning mathematics with high strengths and potentials in integrating characters into learning scenarios to be able to improve students' problem-solving skills and develop their character containing Subject-Specific Pedagogic.